2023
DOI: 10.3390/v15030621
|View full text |Cite
|
Sign up to set email alerts
|

Immunisation against COVID-19 in Pregnancy and of Women Planning Pregnancy

Abstract: Following reports of the first human SARS-CoV2 infection in December 2019 from Wuhan Province, China, there was such rapid spread that by March 2021, the World Health Organization (WHO) had declared a pandemic. Over 6.5 million people have died from this infection worldwide, although this is most likely an underestimate. Until vaccines became available, mortality and severe morbidity were costly in terms of life lost as well as the cost of supporting the severely and acutely ill. Vaccination changed the landsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 121 publications
0
3
0
Order By: Relevance
“…About this, Konje et al have stated that the transplacental transfer of antibodies starts in the second trimester. 30 Similarly, Kugelman et al…”
Section: Discussionmentioning
confidence: 94%
“…About this, Konje et al have stated that the transplacental transfer of antibodies starts in the second trimester. 30 Similarly, Kugelman et al…”
Section: Discussionmentioning
confidence: 94%
“…Studies and research have shown that the COVID-19 vaccine provides numerous benefits to pregnant women, including a reduced risk of hospitalization and death for the mother, and transmission of neutralizing antibodies to the fetus that confers disease protection after birth [ 60 , 67 ]. Pregnant individuals with beliefs that the COVID-19 vaccine carried benefits were less vaccine-hesitant and more likely to be vaccinated against COVID-19 or report an intent to vaccinate [ 36 , 68 , 69 ].…”
Section: The 5-p Vaccine Acceptance Model In Pregnancymentioning
confidence: 99%
“…Post-COVID-19 vaccination, elevated coagulation indexes (D-Dimer levels) may be associated with infrequent thromboembolic events during pregnancy [8][9][10]. Furthermore, beyond the pediatric population, pregnancy may be linked to infrequent covid-19 vaccine-induced potentially fatal complications, including myocarditis and/or thrombocytopenia, although these are infrequent and require further clarification [11].…”
Section: Introduction 1potential Impact Of Covid-19 and Vaccination O...mentioning
confidence: 99%